Pendidikan Akhlak dalam “Khadijah” Karya Abdul Mun’im Muhammad Umar - Oeky Diasworo; Mukroji (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Morals play a central role in forming relationships, both between humans and Allah SWT and with fellow humans. Humans have moral standards to regulate good and bad behavior. One way to teach morals is through studying the history and biography of the life of Khadijah bint Khuwailid in the book Khadijah by Abdul Mun'im Muhammad Umar. Khadijah is a role model who inspires various groups. Through his life story, moral values can be learned better. From this background, the main questions that arise are what is the personality of Khadijah bint Khuwalid, what is the concept of moral education contained in Khadijah's book, and its relevance to Islamic education in the current era. The aim of this research is to understand Khadijah's personality, understand the concept of moral education in Khadijah's book, and understand its relevance to education in the current era. In this research, the researcher applies library research methods with a qualitative approach, which examines in detail the object being researched. The approach method applied is descriptive analysis. The author uses Gadamer's hermeneutical analysis approach theory in order to gain a deeper understanding of the moral values contained in Khadijah's book. The research results show that the value of moral education in Khadijah's book includes morals towards Allah (such as monotheism, piety, remembrance, trust, and gratitude), morals towards oneself (including patience, trust, maintaining personal purity, honesty, keeping promises, and steadfastness) , as well as morals towards others (doing good and generosity). These values are very relevant to current education, in accordance with the national goal of forming a personality who is faithful, devout and has noble character. Therefore, the moral values in Khadijah's book can be a guide in the world of education today.